Insights into Enhanced Capacitive Behavior of Carbon Cathode for Lithium Ion Capacitors: The Coupling of Pore Size and Graphitization Engineering - Zou, Kangyu; Cai, Peng; Wang, Baowei; Liu, Cheng; Li, Jiayang; Qiu, Tianyun; Zou, Guoqiang; Hou, Hongshuai; Ji, Xiaobo (Nano-Micro Letters, 2020)
The lack of methods to modulate intrinsic textures of carbon cathode has seriously hindered the revelation of in-depth relationship between inherent natures and capacitive behaviors, limiting the advancement of lithium ion capacitors (LICs). Here, an orientated-designed pore size distribution (range from 0.5 to 200 nm) and graphitization engineering strategy of carbon materials through regulating molar ratios of Zn/Co ions has been proposed, which provides an effective platform to deeply evaluate the capacitive behaviors of carbon cathode. Significantly, after the systematical analysis cooperating with experimental result and density functional theory calculation, it is uncovered that the size of solvated PF6− ion is about 1.5 nm. Moreover, the capacitive behaviors of carbon cathode could be enhanced attributed to the controlled pore size of 1.5–3 nm. Triggered with synergistic effect of graphitization and appropriate pore size distribution, optimized carbon cathode (Zn90Co10-APC) displays excellent capacitive performances with a reversible specific capacity of 50 mAh g−1 at a current density of 5 A g−1. Furthermore, the assembly pre-lithiated graphite (PLG)//Zn90Co10-APC LIC could deliver a large energy density of 108 Wh kg−1 and a high power density of 150,000 W kg−1 as well as excellent long-term ability with 10,000 cycles. This elaborate work might shed light on the intensive understanding of the improved capacitive behavior in LiPF6 electrolyte and provide a feasible principle for elaborate fabrication of carbon cathodes for LIC systems. Highlights: 1 Pore size and graphitization engineering of carbon cathode were orientated-designed by regulating the molar ratios of Zn/Co ions. 2 Zn90Co10-APC and its assembled PLG//Zn90Co10-APC LIC both deliver the excellent electrochemical performances.